Efeito do óxido de molibdênio sobre as propriedades catalíticas do sistema Fe2O3/Al2O3 frente a reação de desidrogenação do etilbenzeno - Lima, José Gerlande Silva (2019)
Catalysts composed of aluminum, iron and molybdenum oxides were synthesized by thermal decomposition of the precursor salts at 600 °C. Molybdenum was added with the purpose of evaluating its effect on the structure and catalytic stability of Fe2O3/Al2O3 in the reaction of dehydrogenation of ethylbenzene. The samples were characterized by various techniques: X-Ray Fluorescence (XRF), X-Ray diffraction (XRD), Nitrogen adsorption-desorption isotherms, Fourier-transform infrared (FTIR) spectroscopy, Scanning electron micrographs (SEM), temperature-programmed desorption of CO2 (CO2-TPD), Temperature-programmed reduction technique (TPR), Thermogravimetric analysis (TGA) and Differential thermal analysis (DTA). The catalytic performance test in the dehydrogenation reaction of ethylbenzene was carried out in the gas phase, using inert (N2) and oxidant (N2/CO2) atmosphere. The effect of catalytic pretreatment conditions was also evaluated by modifying the inert (N2) or reductive (H2) atmosphere. It was observed that the addition of CO2 in the feed stream promoted an improvement in the conversion and selectivity for the catalysts containing molybdenum oxide (MoAl and FeMoAl), and had little effect for the FeAl catalyst. Partial reduction of the catalysts, pretreatment under H2 flow, affected the styrene selectivity of the MoAl sample, which is consistent with the small increase in styrene conversion. However, the previous reduction of the FeMoAl sample affected the conversion with small increasing of selectivity to styrene. The addition of CO2 did not result in an effective decrease in coke deposition in any of the catalysts studied. However, the use of CO2 together with molybdenum oxide resulted in higher catalytic stability.